Auxillia Mnangagwa's “Amaihood” and the cultural politics of the Zimbabwean first lady in the “New Dispensation” - Saidi, Umali (Routledge, 2022)
Grace Mugabe’s Amaihood (mother of the nation) was despised in hegemonic discourses of (il)legitimacy in the last days of Robert Mugabe’s rule. Her political ascension in ZANU PF and national leadership was supported by ZANU PF’s Youth and Women’s Leagues which, among other things, recommended and advocated for her candidacy to succeed her now late husband. The two vice presidents, Joice Mujuru and later the embattled Emmerson Mnangagwa, were accused by Grace Mugabe and her supporters of harbouring presidential ambitions and her active role resulted in the two (Joice Mujuru in 2014; Emmerson Mnangagwa in 2017) being fired from the party. Emmerson Mnangagwa replaced Joice Mujuru only to be fired from the same post in 2017. Grace Mugabe’s behaviour and speeches, viewed in patriarchal political circles as vulgar and disconnected from the nation, also questioned core ethical and traditional values. The 2017 military intervention, premised on the call to ‘restore legacy’, further exposed the direct involvement of the military in ZANU PF and Zimbabwean politics. However, ‘disgraced’ by her husband’s forced resignation in November 2017, Grace Mugabe’s role as ‘mother of the nation’ was, as it were, replaced by Auxillia Mnangagwa following elevation of Emmerson Mnangagwa to lead the ‘new’ dispensation. Drawing from semiotics and Critical Discourse Analysis (CDA), therefore, this chapter uses Auxillia Mnangagwa’s politico-cultural performance of Amaihood to examine cultural politics of her re-invention of ‘Amaihood’ in the ‘Second Republic’.